Longitudinal Pathways for the Maintenance of Non-Suicidal Self-Injury in Adolescence: The Pernicious Blend of Depressive Symptoms and Self-Criticism - Xavier, Ana (2017)
BACKGROUND: Non-suicidal self-injury is a serious and alarming phenomenon during adolescence. There is a need for understanding the intrapersonal variables that might contribute to the maintenance of these self-injurious behaviors. OBJECTIVE: This study aims to concurrently compare intrapersonal variables between adolescents with and without a lifetime history of non-suicidal self-injury, and to longitudinally test whether non-suicidal self-injury over lifetime history predicts 6-months non-suicidal self-injury through self-criticism and depressive symptoms among Portuguese adolescents with a self-reported history of non-suicidal self-injury. METHODS: Adolescents (N = 418, 12-19 years-old) from middle and secondary schools completed self-report questionnaires to assess self-criticism (particularly, the most severe form: hated self), depressive symptoms, and the frequency of non-suicidal self-injury in two points in time over the 6-month interval. RESULTS: Adolescents who reported a lifetime history of NSSI tend to experience greater harsh and persecutory criticism towards themselves and elevated depressive symptoms than adolescents without a history of NSSI. Results from path analysis showed that lifetime non-suicidal self-injury predicts subsequent non-suicidal self-injury, and this association is mediated by self-hatred and depressive symptoms among adolescents with lifetime non-suicidal self-injury. CONCLUSIONS: Findings suggest that non-suicidal self-injury is maintained through a sense of self-focused on hatred and disgust feelings and depressive symptoms.